CHINA'S SOFT POWER DIPLOMACY IN INTERNATIONAL POLITICS: STRATEGIES, MEANS AND IMPLICATIONS - Chandra, Ramesh; Sinha, Manasi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The concept of soft power has become increasingly significant in the realm of international politics. As nations seek to exert their influence on the global stage, the ability to shape the preferences and perceptions of others through non-coercive means has emerged as a vital tool. China, with its rapidly growing economic and political clout, has substantially engaged in exercising strategies and means as soft power politics to accomplish its presence in the global politics. This research paper examines China's soft power diplomacy in international politics, focusing on the strategies and means employed by the Chinese government to enhance its global influence. The primary objective of this research is to investigate how China strategically employs soft power and assess the implications of these strategies on international politics. To achieve this, the study utilizes a qualitative approach, considering key indicators such as culture, diplomacy, education, and public opinion. By examining China's soft power initiatives and their effects, this research sheds light on the evolving dynamics of international politics in the 21st century, where soft power plays a significant role in shaping global perceptions and relations